Implementasi Manajemen Risiko Pada Keberlanjutan Usaha Bumdes Temmapettue: Studi pada Desa Teamalala Kecamatan Ulaweng - Suci Aryuningsih; Abd. Rasyid R; Sitti Nikmah Marzuki (Faculty of Islamic Economics and Business, 2026)
Village-Owned Enterprises (BUMDes) play a strategic role in promoting rural economic development; therefore, effective risk management is essential to ensure business sustainability. This study aims to analyze the implementation of risk management, business development, and the challenges encountered by BUMDes Temmapettue in Teamalala Village, Ulaweng District, Bone Regency. The research employed a qualitative approach, with data collected through observation, interviews, and documentation, and analyzed using descriptive qualitative methods. The findings indicate that risk management has been implemented through continuous risk identification, assessment, control, and evaluation, which has contributed significantly to the development and sustainability of the enterprise. The implementation of risk management has strengthened operational performance, improved managerial capability, and enhanced the management's confidence in the long-term prospects of the business. Nevertheless, several challenges remain, including delays in the supply of raw materials and minor workplace injuries experienced by employees during the production process. In conclusion, the implementation of risk management plays a crucial role in supporting the sustainability of BUMDes Temmapettue. However, continuous improvements in risk mitigation strategies are necessary to ensure the long-term resilience and sustainability of the enterprise.